Passive optical network architecture based on waveguide grating routing. - Banerjee, D.
We explore an optical network architecture which employs dense wavelength division multiplexing (WDM) technology and passive waveguide grating routers (WGRs) to establish a virtual topology based on lightpath communication. We examine the motivation and the technical challenges involved in this approach, propose and examine the characteristics of a network design algorithm, and provide some illustrative performance results
Keywords: WDM; Dense wavelength division multiplexing; Fault tolerant network; Lightpath communication; Network design algorithm; Passive optical network architecture; Passive waveguide grating routers; Performance results; Virtual topology; Waveguide grating routing